Ameliorative Effects of Moringa Oleifera on Histomorphology of Rat Testis Treated with Fluoxetine - Ali, Ayesha; Qamar, Abdullah; Hamid, Shabnam; Faisal, Tayyaba; Khurshid, Tooba; Mushtaq, Fareeha (Pakistan Armed Forces Medical Journal, 2023)
Objective: To observe the histomorphological changes in rat testes treated with Fluoxetine, focusing on the weight of the testis along with the epithelial thickness of the seminiferous tubules and evaluating the ameliorative effects of Moringa oleifera on the same gross and histological parameters.Study Design: Laboratory-based experimental study.Place and Duration of Study: Army Medical College, National University of Medical Sciences (NUMS), with the National Institute of Health, Islamabad and Pak Emirates Military Hospital, Rawalpindi Pakistan, from Sep 2022 to Mar 2023.Methodology: Thirty male Sprague Dawley rats divided into three groups (n=10). Group-A was the Control-Group, and the rest served as the Experimental-Group. Drugs were given in a single daily dose through oral gavage for eight weeks. Group-B was given Fluoxetine, 10 mg/kg body weight. Group-C was administered Fluoxetine in the same dose and concomitant administration of Moringa powder, 50mg/30 grams body weight. After sacrifice, testes were fixed and stained with Hematoxylin and Eosin for histological study.Results: The study found a statistically significant decrease in the weight of rat testis (p-value˂0.05) and epithelial thickness of seminiferous tubules of rats treated with Fluoxetine (p-value ˂0.05). Conclusion: Fluoxetine significantly decreased the weight of the testis and epithelial thickness of the seminiferous tubules in rat testes. Moringa Oleifera administration ameliorated these effects in the short term.